Corporate sustainability management accounting and multi-level links for sustainability – A systematic review - Stefan Schaltegger; Katherine L. Christ; Julius Wenzig; Roger L. Burritt (International Journal of Management Reviews, 2022)
The societal vision of sustainable development changes both the context of businesses and expectations that management should contribute to solving sustainability problems beyond organizational boundaries. Companies are influenced by macro-level developments such as new environmental regulations and by meso-level context such as social industry standards and guidelines. At the same time, companies are expected to contribute to sustainability transformations of markets at the meso-level and to solving grand sustainability problems at the macro-level such as the greenhouse effect. These developments increase and change sustainability information needs of managers and management accounting. This paper provides a systematic literature review of how sustainability management accounting (SMA) addresses links with the organization's contexts and contributions to sustainability transformations beyond organizational boundaries. The analysis questions the conventional assumption of an internal scope for SMA. It recognises this as a problematic constricting assumption in the literature and, instead, proposes a multi-level Context, Action-formation and Transformative contributions (CAT) framework for further development of SMA.
Keywords: 650